2010
DOI: 10.1242/dev.045088
|View full text |Cite
|
Sign up to set email alerts
|

The leading edge during dorsal closure as a model for epithelial plasticity: Pak is required for recruitment of the Scribble complex and septate junction formation

Abstract: SUMMARYDorsal closure (DC) of the Drosophila embryo is a model for the study of wound healing and developmental epithelial fusions, and involves the sealing of a hole in the epidermis through the migration of the epidermal flanks over the tissue occupying the hole, the amnioserosa. During DC, the cells at the edge of the migrating epidermis extend Rac-and Cdc42-dependent actin-based lamellipodia and filopodia from their leading edge (LE), which exhibits a breakdown in apicobasal polarity as adhesions are sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 69 publications
5
58
0
Order By: Relevance
“…Recent evidence suggests that microRNA target sites with a previous report in a tissue culture model for cardiac hypertrophy showing that sarcomere units are misassembled in cultured rat cardiomyocytes when Cdc42 expression is disrupted (Nagai et al, 2003;Brown et al, 2006). In addition, Cdc42 in Drosophila interacts with a known downstream effector of Cdc42, Pak, which participates in actin filament assembly and dynamics (Harden et al, 1996;Bahri et al, 2010), thus consistent with a possible role for Cdc42 in myofibrillar organization. Similar to our Cdc42;Nkx2-5 compound heterozygote analysis, it has been shown that mice transheterozygous for loss-of-function alleles of Nkx2-5 and Tbx5 also exhibit a synergistic interaction, in particular with respect to the development of the cardiac conduction system (Moskowitz et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Recent evidence suggests that microRNA target sites with a previous report in a tissue culture model for cardiac hypertrophy showing that sarcomere units are misassembled in cultured rat cardiomyocytes when Cdc42 expression is disrupted (Nagai et al, 2003;Brown et al, 2006). In addition, Cdc42 in Drosophila interacts with a known downstream effector of Cdc42, Pak, which participates in actin filament assembly and dynamics (Harden et al, 1996;Bahri et al, 2010), thus consistent with a possible role for Cdc42 in myofibrillar organization. Similar to our Cdc42;Nkx2-5 compound heterozygote analysis, it has been shown that mice transheterozygous for loss-of-function alleles of Nkx2-5 and Tbx5 also exhibit a synergistic interaction, in particular with respect to the development of the cardiac conduction system (Moskowitz et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…cells, neurons, and epithelial cells (Genova et al, 2000;Jacinto et al, 2000;Jhaveri and Rodrigues, 2002). During Drosophila dorsal closure, Cdc42 activates the serine/threonine protein kinase Pak to regulate dynamic actin structure and epithelial plasticity (Harden et al, 1996;Bahri et al, 2010). Therefore, we reasoned that Cdc42 may act through the Pak pathway to regulate actin filament assembly and thus myofibrillar structure in the fly heart.…”
Section: Cdc42 Interacts With Nkx2-5 In Modulating Adult Mouse Heart mentioning
confidence: 99%
“…Recently however, the Scrib complex has been reported to be recruited to the leading edge of migrating epithelial cells during dorsal closure of the Drosophila embryo, whereas it is relocalized to the lateral membrane to promote the restoration of apico-basal polarity on closure. Through differential localization and binding partners, Scribble apparently acts as a molecular switch, allowing epithelial cells to alternate between an apical-basal adhesive state and a migratory state during epithelial-to-mesenchyme transition (29). In mature T cells, Scribble is localized to the uropod in migrating cells and temporarily relocalizes to sites of contact on interaction with antigen-presenting cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that Pak, a group I Pak protein, participates in development of the follicular epithelium (FE) surrounding the Drosophila egg chamber through regulation of the actin cytoskeleton and apicobasal polarity (Conder et al 2007;Bahri et al 2010). In middle-stage egg chambers, the F-actin network polarizes to the basal end of the follicle cells where it forms bundles of filaments aligned perpendicularly to the anterior-posterior (A-P) axis of the egg chamber (Gutzeit 1990(Gutzeit , 1991Gutzeit and Haas-Assenbaum 1991).…”
mentioning
confidence: 99%